QUATERNARY SHELF SEA PALAEOCEANOGRAPHY: RECENT DEVELOPMENTS IN EUROPE - Scourse J.D.; Austin W.E.N. (My University, 2002)
High-quality palaeoceanographic reconstructions based on sequences preserved in shallow marine environments demonstrate that these constitute significant archives of climatic and oceanographic change. Such sequences are important, first, because their often very high-resolution, sometimes laminated, nature enables high-frequency cycles to be resolved and provides the basis for establishing spatial and temporal variability in the marine radiocarbon reservoir effect. Second, sea-level index points from shelves are important for the validation of glacio-hydro-isostatic geophysical models and for understanding sea-level change during early deglaciation. Third, shallow marine sequences contain excellent records of land-ocean interaction, often preserving paired terrestrial-marine proxies in the same stratigraphic sequence. A new development in shelf sea palaeoceanography is documenting the long-term dynamics of shelf sea stratification. This is the dominant hydrodynamic phenomenon of tide-dominated shelf seas in the middle and high latitudes and has a profound influence on productivity and therefore global change through the carbon cycle. Detailing the evolution of seasonal stratification during eustatic highstands is therefore of relevance to the climate system.
Keywords: PALAEOCEANOGRAPHY; SHELF SEA; RADIOCARBON; ISOSTATIC MODELLING; SEASONAL STRATIFICATION; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная